A social media-based intervention to support the management of adolescents with Type 1 Diabetes Mellitus - Mc Darby, Vincent (Trinity College (Dublin, Ireland). School of Psychology, 2016)
Chapter 1 described diabetes, its incidence rate and the difference between Type 1 Diabetes Mellitus (T1DM) and Type 2 Diabetes Mellitus (T2DM), with a focus on T1DM. Management of T1DM is very demanding process that places a significant burden on individuals. Failure to adhere to recommended diabetes management advice can lead to both acute and chronic health problems. Adherence difficulties are common in T1DM and are particularly common during adolescence. The awareness of the problem of poor adherence has led to research aimed at psychological correlates and predictors of adherence. Social cognitive theory, including self-efficacy, self-regulation and illness perceptions, has been used to frame the problem of adherence in T1DM. Chapter 2 examined the impact of social support on the adherence of adolescents with T1DM. Positive parental social support has been found to be associated with better glycaemic control. The influence of peers has also been found to impact on the adherence of adolescents with T1DM and this can be positive or negative depending on the nature and context of the peer support. There is very little research on influence of social support from T1DM peers on adolescents with T1DM; however, research on support from peers with similar medical conditions suggests that it could be beneficial. Social support from the diabetes healthcare team (DHCT) is another source of support for individuals with T1DM that warrants further research. Research on patient-centred communication and autonomy support suggests that it could hold significant efficacy. Chapter 3 examined the potential of social network sites (SNS) in the management of T1DM. The role of SNS in healthcare is becoming ubiquitous and this has led to the proliferation of online patient expert groups. A number of research studies have suggested that SNS could be a useful tool in supporting adolescents with T1DM, however; there has been very little research on the efficacy of SNS in adolescent diabetes management. Chapter 4 outlines the rational and aims of the present study. A social media based intervention (SMBI) was developed and administered via a SNS that targeted increasing the support adolescents receive from the DHCT and from T1DM peers with the aim of improving glycaemic control and quality of life. Chapter 5 described a pilot study that was undertaken where the SMBI was designed, implemented and evaluated. Chapter 6 outlines the methodology employed in the current study to investigate the efficacy of the SMBI and included both quantitative and qualitative analysis. Chapter 7 looks at the results of the quantitative analysis of the SMBI. The SMBI was not found to have had any significant impact on glycaemic control or quality of life. The SMBI was found to result in an increase in diabetes specific knowledge. Chapter 8 examined that qualitative analysis of the SMBI. Participants found the SMBI to be a very positive experience and noted increased support from the DHCT and T1DM peers as a result of the SMBI. Chapter 10 integrated the findings of the thesis and discussed the implications for understanding interventions to improve adherence in adolescents with T1DM. Limitations of the research were discussed and directions for future research suggested. Finally the conclusions of the thesis are presented.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin